STRATEGI PEMASARAN MUSEUM BENTENG VREDEBURG YOGYAKARTA UNTUK MENINGKATKAN JUMLAH PENGUNJUNG - , EVA APRIL LILIYANA, Fahmi Prihantoro, S.S, S.H, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Museum is a permanent institution, not for profit, and serves to convey information to the public. Therefore, to increase the interest of the public to visit the museum needed a specific strategy to market the museum. So the museum can be the interesting place for visitors. Marketing strategy is a way of managing strategic partnerships and positioning the company among the sellers and buyers. So in the context of marketing strategy managing the museum, the museum had to adjust or reposition themselves in development between the ideas with the community manager of the museum. Activities to accommodate the museum marketing strategy can be done with the study of museum visitors. Additionally Vredeburg Museum also aims to revitalize that provide comfort to visitors. And also do promotions like Travel Dialog, Talk Show, Seminar, Culture camp, and Temporary Exhibition.